Studi Fenomenologi Perilaku Remaja Putri dalam Mengatasi Dismenore - Alika Nurul Hidayah; Ramli, Rahmawati; Ernasari; Jama, Fatma (Window of Nursing Journal, 2024)
Dysmenorrhea is a complex phenomenon in the human body that occurs due to uterine contractions characterized by an increase in prostaglandins, which can cause a feeling of discomfort. about 89.5% experience menstrual pain disorders, especially for developing countries. This study aims to how the behavior of adolescent girls in overcoming dysmenorrhea in SMA Negeri 4 Enrekang. The design of the study used is a qualitative research design with a total of informants that is 9 people in the area of SMA Negeri 4 Enrekang the results of this study indicate that there are symptoms experienced when informants experience dysmenorrhea namely, impaired activity, lack of concentration in class, emotional disturbances, fainting, and bleeding and behavior of adolescent girls in overcoming dysmenorrhea namely, knowledge, attitudes, and actions. The conclusion of this study is that it has been known that the experience experienced when adolescent girls experience dysmenorrhea include symptoms at the time of experiencing dysmenorrhea and there is the behavior of adolescent girls in overcoming dysmenorrhea. Expected for young women, especially those who have been told about how to handle dysmenorrhea and able to handle when there is pain during menstruation.